Adherence to topical therapies in actinic keratosis: A literature review. (1st November 2016) - Foley, Peter; Stockfleth, Eggert; Peris, Ketty; Basset-Seguin, Nicole; Cerio, Rino; Antonio Sanches, José; Guillen, Carlos; Farrington, Emily; Lebwohl, Mark
Abstract: Background: Actinic keratosis (AK) is a common skin condition, for which topical therapies are frequently prescribed. This review summarises current understanding of patient adherence and persistence to topical AK treatment by identifying literature relating to measures of adherence and persistence and influencing factors. Methods: A multi-database literature search was conducted (2004–2015) using key search terms. Supplementary searches of pivotal clinical trials and reference lists of eligible papers were also conducted. Results: Non-adherence and non-persistence rates varied between real-world studies (10–63% and 23–31%, respectively), with combined non-adherence and non-persistence reported as high as 88%. Methods to calculate adherence and persistence differed between studies. Adherence and persistence were generally higher in clinical trials than clinical practice. Key contributing factors to non-adherence and non-persistence to AK treatment were identified as: treatment duration, severity and persistence of local skin responses and patient confusion over treatment regimens. Conclusion: The review highlighted a significant evidence gap regarding adherence and persistence to topical AK therapies. Combined, non-adherence and non-persistence may be as high as 88% in clinical practice, highlighting the importance of incorporating contributing factors to patient non-adherence into treatment decisions.